Branding and brand management - Melewar, T.C.; Syed Alwi, Sharifah Faridah (Henry Stewart Talks, 2012)
What is branding?, Brand elements, Brand association, Brand image, Perceived value, Quality, Brand management, Building brand equity, Sustaining the brand, Key factors to branding, Why branding?, Why organisations brand, New branding challenges, Brand engagement